2020
DOI: 10.1108/mbe-04-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Diversity climate perceptions and its impact on multicultural team innovation and performance

Abstract: Purpose This study aims to examine the influence of diversity climate perceptions (DCPs) on team member’s contribution to team innovation and team performance in a multicultural team (MCT). The authors also investigate the moderating effect of cultural intelligence on these relationships. Design/methodology/approach The authors draw upon the interactional model for cultural diversity to build their hypotheses. Data was gathered from 43 teams consisting of 217 members using a structured questionnaire. Ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The results of the study state that firstly the interaction of lecturers and students of the Sociology Education study program against multicultural symbols results in a student's meaning of multiculturalism which is defined as mutual respect, respect, understanding and knowing the diversity of other people's cultures; The meaning of student multiculturalism is based on multiculturalism; second, the student multiculturalism perspective is formed by a multicultural environment and is inherited from the educational process carried out in the educational environment and family as well as idol figures and students who understand each other (Arbabi et al, 2017;Kadam et al, 2020). Whereas in the internal aspect, the student's multiculturalism perspective can also be formed through self-development with the addition of multiculturalism and thirdly, while the multiculturalism of students in their environment bases their social actions on traditional values, ethics and the values that are used as goals, then there was a positive relationship between an open attitude towards intercultural contact (Haenni Hoti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study state that firstly the interaction of lecturers and students of the Sociology Education study program against multicultural symbols results in a student's meaning of multiculturalism which is defined as mutual respect, respect, understanding and knowing the diversity of other people's cultures; The meaning of student multiculturalism is based on multiculturalism; second, the student multiculturalism perspective is formed by a multicultural environment and is inherited from the educational process carried out in the educational environment and family as well as idol figures and students who understand each other (Arbabi et al, 2017;Kadam et al, 2020). Whereas in the internal aspect, the student's multiculturalism perspective can also be formed through self-development with the addition of multiculturalism and thirdly, while the multiculturalism of students in their environment bases their social actions on traditional values, ethics and the values that are used as goals, then there was a positive relationship between an open attitude towards intercultural contact (Haenni Hoti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The language barrier has caused an avoidance between the staff who has the tendency of not giving any feedback to others when an issue raised to be solved. Kadam et al, (2020) also found that there is evidence that team heterogeneity can result in conflicts, discrimination, communication barriers, etc., which in turn can affect team members' performance. Goh & Lee (2018) also consider the discrimination issues that may be encountered in the hospitality industry must be taken seriously, especially in the diverse multicultural hospitality workforce.…”
Section: Resultsmentioning
confidence: 98%
“…Organisations with internalised prejudices, discriminatory practices, or preferential hiring, may experience conflict and discrimination between employees, as well as poorer performance (Roberge & van Dick, 2010). Those which value diversity are more likely to have employees who work together successfully, which also significantly improves innovation, and overall performance (Kadam et al,2020). Similarly, Hofhuis, van der Rijt, and Vlug (2016) also found that when diversity was embraced by the organisation it led to increased job satisfaction and inclusion.…”
Section: Changing the Storywhere Are We Now And What Next?mentioning
confidence: 93%
“…Rather than creating a role which focuses on diversity, they state that the organisation must focus on DEI as a vital mission or as part of their core values, for there to be any consequential change. The workplace environment and perceptions regarding diversity have an influential role on team performance, especially when there are employees from multicultural backgrounds (Kadam, Rao, Abdul, & Jabeen, 2020). Theoretically, it is thought that having employees from diverse backgrounds would create a larger wealth of skills, abilities, and viewpoints that would enable more creativity and innovation at work in comparison to a group of comparable individuals (Duchek, Raetze, & Scheuch, 2020).…”
Section: Changing the Storywhere Are We Now And What Next?mentioning
confidence: 99%